2006
DOI: 10.2466/pr0.98.3.651-661
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Effects of 5-Methoxy-N,N-di(iso)propyltryptamine Hydrochloride (Foxy) on Cognitive Development in Rats

Abstract: The hallucinogenic "designer drug" known as Foxy or Methoxy Foxy and formally know as 5-Methoxy-N,N-di(iso)propyltryptamine hydrochloride (5-MeO-DIPT) is rapidly gaining popularity among recreational users. However, little is known about the consequences of its use on neuropsychological development or behavior. During one of two adolescent periods, the rats were given repeated injections of either saline or 5 mg/kg of 5-MeO-DIPT. Once the animals reached 80 days of age, they were trained and tested on a number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
4
14
0
Order By: Relevance
“…Seizures and EEG abnormalities are associated with cognitive impairments [99101]. Consistent with this, we and others have shown that rats given Foxy (30–80 mg/kg total) resulted in egocentric and spatial learning deficits following treatment [31, 60, 61]. Further research into how Foxy induces seizures is warranted given the present findings.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Seizures and EEG abnormalities are associated with cognitive impairments [99101]. Consistent with this, we and others have shown that rats given Foxy (30–80 mg/kg total) resulted in egocentric and spatial learning deficits following treatment [31, 60, 61]. Further research into how Foxy induces seizures is warranted given the present findings.…”
Section: Resultssupporting
confidence: 88%
“…This experiment determined the EEG profile in rats of three popular drugs of abuse using the exact dosing regimen shown to induce learning and memory deficits [46, 47, 56, 62] and neurochemical changes consistent with those seen in chronic users upon post mortem examination [33, 35, 51, 53, 60, 61]. Both Foxy and MA resulted in altered EEG activity, with Foxy producing more severe effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Foxy induced an increase in the head-twitch response in mice [20]. Rats exposed to Foxy during development demonstrated deficits in response learning [13], spatial learning in the Morris water maze (MWM), and exaggerated hyperactivity following a methamphetamine challenge in adulthood [57]. …”
Section: Introductionmentioning
confidence: 99%